Get your photography on the Web : the fastest, easiest way to show & sell your work - Concepcion, Rafael (Peachpit Press, 2011)
Shows photographers how to set up and maintain a professional-looking website, covering such topics as securing a domain name and hosting space, installing WordPress, adding pictures and galleries, and selling images online